Counseling on how to brush your teeth on behavior changes in preschool children at ra mnu 36 mutmainah, tegal regency - Putri Apriliyana Wahyuningsih; Musri Amurwaningsih; Nira Ardlina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Dental and oral hygiene for brushing their teeth. Often many parents do not learn and practice their personal hygiene. In this study, counseling was carried out on how to brush teeth on behavior in preschool children. Tooth brushing skills must be taught from an early age, especially preschool children who are in a period of growth and development in order to change behavior from those that are detrimental to their health.Method: The research method is Pre-Experimental Design with the research design used is One group pre-test and post-test control design. There are steps, namely initial observation (O1) or pre-test, counseling (providing intervention), final observation (O2) or post-test, and data analysis. The intervention was given to the respondents using a simulation technique using the phantom tooth Bass method where the researcher would observe for 20 days.Result: The results showed that there was a significant effect indicating the significance value of the Wilcoxon was 0.00 (p < 0.05)Conclusion: There is an effect of counseling on how to brush teeth on behavioral changes in preschool children at RA MNU 36 Mutmainah. Respondents have sufficient skill level as much as 1 person (1.5%).